Disseminated herpes simplex infection induced hepatitis during pregnancy mimicking HELLP syndrome, a diagnostic challenge - Hassam Ali; Shruthi Kumar; Mary-Kate Kratzer; Josef Kinderwater (Infectious Medicine, 2022)
The disseminated herpes simplex virus 2 (HSV-2) carries a high mortality rate in pregnant women if left unrecognized. It often presents as unrelieved fever and hepatitis. Diagnosis is challenging due to vague symptoms and potential overlap with other conditions. Pregnancy is a risk factor as it conforms to a partially immunocompromised state. Dissemination to the brain could be devastating, and the treatment requires intravenous antivirals like acyclovir. Fetal outcomes are variable based on previous case reports. We present a case of young female gravida 1 para 1 who presented with disseminated HSV infection mimicking HELLP (Hemolysis, Elevated Liver enzymes, and Low Platelets) syndrome. She responded well to intravenous acyclovir, and the fetus had a viable outcome at the 26th week of gestation. Early diagnosis can prevent progression to fulminant liver failure and the need for a liver transplant.